Existe associação entre as doenças periodontais e O nascimento pré-termo? - FEITOSA, Danielli Maria Zucateli (2017)
Introduction: The association between periodontal disease in pregnant women and the reduction of gestational age is not consolidated in the literature, presenting many aspects of studies. One of the reasons for the divergence of these results is the use of different definitions of periodontitis in periodontal research, which determine distinct prevalences in populations of the world. This thesis aimed to evaluate the possible association between periodontal disease and reduction of gestational age in pregnant women (Chapter 1) and to determine an ideal criterion for the diagnosis of periodontitis (Chapter 2). Methodology: In Chapter 1 was developed a longitudinal study of the cohort type and initially evaluated 1.447 pregnant women with 22 to 25 gestational weeks, of whom 194 were excluded from the sample, totaling 1.253 who underwent oral examination, which included periodontal examination (probing depth: PD ≥ 4 mm with bleeding on probing: BOP at the same site, clinical attachment level: CAL ≥ 4 mm); prenatal physical/medical examinations (height, weight, hypertension and gestational diabetes) and and socioeconomic questionnaire (maternal age, schooling, head of household, income, economic class and smoking). Structural equation modeling analysis was applied to estimate the association between socioeconomic status, maternal periodontal disease (latent variable) and reduction of gestational age. In Chapter 2 a critical review of the literature was made in the electronic databases: Scielo and Medline / Pubmed, using the uniterms: Diagnosis, Classification, Periodontal Diseases, Gingivitis and Periodontitis. Results: The periodontal disease was not associated with the reduction of gestational age (CP: 0.002; p: 0.966), and this outcome was only associated (p <0.05) with hypertensive women (CP: -0.192), obese (CP: -0.079), elderly (CP: -0.074) and with worse socioeconomic conditions (CP: -0.080). Older women (CP: 0.115; p: 0.032) and with worse socioeconomic conditions (CP: -0.107; p: 0.014) had higher prevalence of periodontal disease. It was possible to verify in article 2 that the ideal diagnostic criterion for periodontitis is the one that includes the three clinical parameters most used in epidemiological surveys there are PD, CAL and BOP probing used together, aiming to obtain a profile more in keeping with the reality of the periodontal health of the individual studied. Conclusions: Article 1 reveals the non-association between periodontal disease and reduction of gestational age. Hypertension, pre-gestational body mass index, maternal age and low socioeconomic status act as risk factors for such outcome. And the article 2 confirms that the ideal periodontal criterion for the diagnosis of periodontitis is the combination of probing depth, clinical attachment level and bleeding on probing in the same analysis.